Avaliação do consumo e determinação da mobilidade mineral em bovinos suplementados com fontes quelatadas e inorgânicas de microminerais - Filipe Aguiar e Silva (2017)
One of the ways to verify the efficiency of use of the chelated minerals would be the stability they present in ruminal environment, the way in which they are absorbed and their interaction with other compounds. The objective of this work was to evaluate the consumption of chelated and / or inorganic mineral supplementation as well as the intake of concentrated and bulky food using LIPE®, NANOLIPE®, Titanium Dioxide (TiO2) and Fiber Indigestible Neutral Detergent (NDFI), comparing with traditional methodology, total collection of fecal in crossbred Hostein and Gir animals. The effect of micromineral mobility on liver and blood, excretions in fecal and urine, and ruminal parameters, under different conditions, animals without supplementation, supplemented with inorganic, chelated and inorganic / chelated sources (together) were also evaluated. The results show that for fecal recovery, only the NANOLIPE® indicator was similar to the ideal recovery (100%), in both periods. All indicators were able to estimate fecal production and DM intake. NANOLIPE® and FDNi were able to estimate digestibility (68.12 and 65.46%), respectively, when compared to the apparent digestibility (68.17%) in period 1, in period 2, all indicators were similar to apparent digestibility. In the determination of the differentiated consumption, only NDFI estimated similar results in the determination of the consumption of roughage when compared to the actual consumption for period 1 (4.45 and 4.39 kg / day) and period 2 (4.59 and 4.48 kg / day), respectively. For the concentrate, only the FDNi was different from the actual consumption. In the evaluation of mineral supplement intake, only NANOLIPE® was similar to actual mineral intake. The ruminal parameters, pH, N-NH3, and the production of VFA were not affected by the different treatments. No differences (P> 0.05) were found in the serum concentration of the minerals between the different treatments. The chelated forms of minerals had higher concentrations in the liver. Major urinary excretions of Co from the chelated sources of this element were observed. Fecal excretion of Zn was higher in animals receiving the chelated sources of this element.